Del Barroco a la Ilustración en una fiesta del Antiguo Régimen: el Corpus Christi - Martínez Gil, Fernando; Rodríguez González, ALFREDO (Cuadernos de Historia Moderna, 2002)
The long time evolution of the Corpus Christi feast lets distinguish two confronted forms for understand religiousness. The first one, coming from the Middle Age and in vogue during the baroque centuries, favors the mixture of cultured and popular, religious and profane elements; the second one, which imposes with the Enlightnment in the 18th century, clears the popular aspect from the feast and seizes it in te name of reason, interior religion and social control.